Asexual reproduction and molecular systematics of the sea anemone Anthopleura krebsi (Actiniaria: Actiniidae) - Braga Gomes, Paula; Zamponi, Mauricio Oscar; Solé-Cava, Antonio Mateo (Revista de Biología Tropical, 2003)
In this paper we use allozyme analyses to demonstrate that individuals in Anthopleura krebsi aggregates are monoclonal. Additionally, sympatric samples of the red and the green colour-morphs of A. krebsi from Pernambuco, Brazil were genetically compared and no significant differences were observed between them (gene identity= 0.992), indicating that they do not belong to different biological species. All individuals within aggregates of the green colour-morph were found to be identical over the five polymorphic loci analysed. Such results would be extremely unlikely (P<10-11) if the individuals analysed had been generated through sexual reproduction, thus confirming the presence of asexual reproduction in this species.